Importance of Providing Additional Choices in Relation to Pupils' Happiness, Mastery, Well-Being, Contentment, and Level of Physical Activity in Physical Education - Oldervik, Stian; Lagestad, Pål (Frontiers in Sports and Active Living, 2021)
Previous research points to the importance of providing support to autonomy in PE, because it has a particularly positive effect on motivation in PE. However, previous research has not examined the association between autonomy and the variables; happiness, mastery, well-being, contentment and activity level in PE. This study examined how increased self-determination affects happiness, mastery, well-being, contentment and activity level in PE. The study is an intervention (cross-over study) with one control group (one class) and two intervention groups (two classes), using questionnaires and accelerometers among 88 tenth graders (41 boys and 47 girls). The three classes included approximately the same number of boys and girls. The intervention groups included, respectively, 30 and 29 pupils in each class, and 29 pupils' in the control group. The pupils' experiences of happiness, mastery, well-being, contentment was measured three times–after a month with, respectively, ordinary PE, teacher-directed PE, and self-organized PE (autonomy), and the activity levels (accelerometer) was measured during the 24 lessons that took part in the period of teacher-directed PE and self-organized PE. Factor analysis, repeated measures ANOVA (mixed method ANOVA design) and paired sample t-tests with Bonferroni correction were performed, in order to look at differences in happiness, mastery, well-being, contentment and activity level during periods of; self-determination, teacher-directed PE and ordinary PE. The results show that self-determination in PE gives the pupil a significant increased experience of happiness, well-being and contentment, and also a higher activity level in PE. The results indicate that increased self-determination in PE can positively affect lower secondary school pupils' happiness, well-being, contentment and activity level in PE, and that teachers should strive to encourage self-determination among pupils in PE. Further research should be based on intervention studies studying self-determination over longer continuous period, in classes with both older and younger pupils.